Impacto de um programa de intervenção para mudança do estilo de vida sobre indicadores de aptidão física, obesidade e ingestão alimentar de indivíduos adultos - Ravagnani, Christianne de Faria Coelho [UNESP]; Pereira, Avany Fernandes; Ravagnani, Fabrício César de Paula; Michelin, Edilaine [UNESP]; Corrente, José Eduardo [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 2010)
Lifestyle modification programs (LMP) including physical exercises and nutritional re-education are the recommended conducts for primary atention to non-communicable chronic diseases. Although widely recommended there are just few data available about long time LMP. The present work aimed to present the effects of 2 years LMP on dietary, anthropometric and physical fitness of adults from both gender. One hundred and four subjects (77 women and 27 men; 54.04±7.7 years) fullfiled the inclusion criteria of exercise sessions, presence of nutritional meetings and accomplishment of every 6-months assessments during 2 years. After the clinical trial all subjects were included in supervisioned exercise program of 80 min, 5x/wk along with diet-counseling meetings. Assessments of dietary intake, anthropometry and physical tests were undertaken semesterly. Statistical analysis were done to compare sexes, aging and moments for α=5%. Six months of LMP reduced significantly body weight and body mass index and more markedly physical unfitness without changes on food intake. Only trunk flexibility and handgrip continued to improve up to 24 mo. The greater improvements were found in women. Thus the present long-lasting LMP showed to be efficient for adults in promoting better physical fitness and body fat reclassification without signifi cant dietary changes.

Lifestyle modification programs (LMP) including physical exercises and nutritional re-education are the recommended conducts for primary atention to non-communicable chronic diseases (NCCD). Although widely recommended there are just few data available about long time LMP. The present work aimed to present the effects of 2 years LMP on dietary, anthropometric and physical fitness of adults from both sexes. One hundred and four subjects fullfiled the inclusion criteria of 3-5x/wk exercise sessions, presence of nutritional meetings and accomplishment of every 6-months assessments during 2 years. After the clinical trial all subjects were included in supervisioned aerobic (60-70%VO2max) exercise program of 80 min, 5x/wk along with diet-counseling meetings. Assessments of dietary intake, anthropometry and physical tests were undertaken semesterly. Statistical analysis were done to compare sexes, aging and moments for α=5%. Six months of LMP reduced significantly BW and BMI and more markedly physical fitness without changes on food intake. Only trunk flexilibity and handgrip continued to improve up to 24 mo. The greater improvements were found in women. Thus the present long-lasting LMP showed to be efficient for adults in promoting better physical fitness and body fat reclassification without significant dietary changes.
Impact of lifestyle change intervention program on physical fi tness, obesity and food intake indicators in adults
Keywords: Physical exercise; Strength; Dietary advice; Body composition; Obesity; Exercício físico; Força; Aconselhamento nutricional; Composição corporal; Obesidade